Effets de l'entraînement pliométrique sur les propriétés mécaniques et géométriques du système muscle-tendon des fléchisseurs plantaires - Ben Jeddou, I.; Yahia, A. R.; Rahali, H.; Dziri, C.; Ben Salah, F. Z. (Science & Sports, 2018)
Objective: To determine the effects of 10 weeks of plyometric training on the geometric parameters of muscle and tendon structures plantar flexors of the ankle and stiffness different elastic components. Methods and materials: Sixty two subjects were randomly divided into a training group (GE) : n=31 ; taekwondoists 5, boxers 6, wrestlers 5, 7 and 8 jumpers in lengths basketball: 20.9±2.6 years, 178.1±8.3cm, 68.4±9.2kg) and control group (CG) : n=31 ; military sports school students: 23.6±1.8 years, 176.6±11.4cm, 72.0±7.7kg. All subjects were involved in regular physical activity (10.5±6.2hours / week) and have not changed their usual activity during the study period. The three experimental sessions were performed in random order one to two weeks before the start of training protocol (pretest) and then a week after the end of the 10 weeks of training (posttest). Results: The main results show few adaptation geometrical properties compared to the mechanical properties of the muscle and tendon plantar flexors ankle. A significant interaction between the "group" and "test" factors was found for squat jump, jumping, multi-hop, maximum voluntary contraction and maximal joint amplitude performance. No significant changes were found for the other parameters. Conclusion: 10 weeks plyometric training have changed the vertical jump performance, flexibility and strength trained subjects. This performance changes in relaxation and strength in particular may be associated with the reduction in rigidity of the active fraction of the elastic component series, the increase in stiffness of the passive portion of the elastic component series well as reduction in dissipation factor of the Achilles tendon.